2008
DOI: 10.1038/leu.2008.169
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of glutathione S-transferase polymorphisms in acute myeloid leukemia

Abstract: Glutathione S-transferases (GSTs) are phase II detoxification enzymes involved in the metabolism of carcinogens and anticancer drugs, known also to interact with kinase complexes during oxidative or chemical stress-induced apoptosis. We were interested whether their polymorphic variants may account for differences in outcome of patients with acute myeloid leukemia (AML) following chemotherapy. We studied the prognostic role of polymorphisms in three GST genes (GSTP1/M1/T1) in a large patient cohort of the Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 41 publications
1
18
0
1
Order By: Relevance
“…To view in colour online please go to: www.informaworld.com/glal were found to be associated with an increased risk of acute leukemia. Such individuals have an impaired ability to detoxify carcinogens, thus, carrying an increased risk of developing cancer [6][7][8][9]. Results of various studies have been contradictory with respect to the role of GST genes in AML [7,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To view in colour online please go to: www.informaworld.com/glal were found to be associated with an increased risk of acute leukemia. Such individuals have an impaired ability to detoxify carcinogens, thus, carrying an increased risk of developing cancer [6][7][8][9]. Results of various studies have been contradictory with respect to the role of GST genes in AML [7,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Similar mechanism has also been described for GSTT1 enzyme (GSTy subfamily) [5]. The gene coding for GSTP1 (GSTp subfamily), displays polymorphisms in its coding region at codons 105 (Ile!Val) and 114 (Ala!Val) which confer different catalytic activities based on the polymorphism [7][8][9].…”
Section: Introductionmentioning
confidence: 88%
“…Genetic polymorphisms in glutathione-S-transferases, such as GSTT1 and GSTM1 , have been widely studied for their associations with drug toxicity, drug response and disease risk in leukemia patients 29,39,42 . Notably, GSTM1 and GSTT1 deletions have been implicated in various phenotypes associated with leukemia including drug response 43 , busulfan pharmacokinetics 28 and disease risk 44 . Although we did not examine the effect of the GSTM1 deletion in this study, we identified several SNPs (genotyped and imputed) in the GSTM1 - GSTM5 locus (rs3754446, rs929166 and rs11101989) associated with DFS in individuals of European ancestry that have not been previously reported (Table 2, Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances to oxidative stress metabolism are commonly associated with tumor cells, and the level of oxidative stress among patients increases with disease severity and the accumulation of chromosomal aberrations (22,23). Leukemias originate from hematopoietic stem cells that lose the capacity to differentiate normally into mature blood cells (24,25).…”
Section: Discussionmentioning
confidence: 99%